A COMPARATIVE STUDY BETWEEN ANITA DESAI AND KIRAN DESAI - Kumar Singh, Krishna (International Journal of Multidisciplinary Research and Studies, 2020)
Kiran Desai and her sister Anita Desai are two of the most well-known authors in Indian English literature. Kiran Desai is the daughter of the renowned writer Anita Desai, who shifted the focus of the Indian novel written in English from its sociopolitical obsessions to the investigation of an individual’s psyche and fundamental human relationships in the years following India’s independence. Kiran Desai is also a successful author in her own right. In the year 1937, Anita Desai was born in Moussurie. She was born in Germany to a mother who was German and a father who was Bengali. The many civilizations, cultures, and customs that her parents come from are evident in her upbringing. These various cultures and customs have a significant impact on the way that she writes. Her formative years were spent in Delhi, and in particular, in old Delhi.